IMPLEMENTASI METODE DESIGN THINKING PEMASARAN DIGITAL PADA UMKM BAHAN TEKSTIL TEXTWILL - Wahyudi, Hegel; Sasetio, Jalalludin; Fikriy, Mohamad; Nurfauzan, Nabil; Nurlela, Siti (Jurnal Pariwisata Bisnis Digital dan Manajemen, 2023)
Digital Marketing is an essential activity in line with the rapid development of Technology, Information, and Communication. Social media content has become one of the means for digital marketing. Social media enables businesses to reach a wider consumer base, provide information about a product more efficiently, and facilitate online transactions, thereby increasing sales and revenue. The issue faced by Textwill is that they still use conventional marketing methods, necessitating promotion through social media as a means of reaching a larger consumer audience. In implementing digital marketing through social media, the right strategy indohoki77 system guarantees that sophisticated security is also implemented to prevent accidents or unethical actions in the gameis required to achieve business goals. The Design Thinking method, which focuses on the needs of businesses or consumers, can be an appropriate approach in designing digital marketing strategies. This research aims to implement the Design Thinking method into Textwill's social media digital marketing, resulting in promotional efforts that align with the needs of the business. The findings of this research show that the established social media presence has not yet yielded significant sales results, but the developed promotional strategies align with the desires of the business.